Inflammatory Bowel Disease Adversely Impacts Colorectal Cancer Surgery Short‐term Outcomes and Health‐Care Resource Utilization. Issue 11 (November 2017) - Ramsey, Mitchell; Krishna, Somashekar G; Stanich, Peter P; Husain, Syed; Levine, Edward J; Conwell, Darwin; Hinton, Alice; Zhang, Cheng
Abstract : OBJECTIVES: : Inflammatory bowel disease (IBD) is associated with an increased risk of colorectal cancer (CRC) compared to patients without IBD. There is a lack of population‐based data evaluating the in‐patient surgical outcomes of CRC in IBD patients. We sought to compare the hospital outcomes of CRC surgery between patients with and without IBD. METHODS: : We used the National Inpatient Sample (2008–2012) and Nationwide Readmissions Database (NRD, 2013) and selected all adult patients (age ≥18 years) with ulcerative colitis (UC) or Crohn's disease (CD) who underwent CRC surgery. Multivariate analysis for in‐patient outcomes of postoperative complications, health‐care resource utilization, readmission rate, and mortality were performed. RESULTS: : A total of 397, 847 patients underwent CRC surgery from 2008 to 2012, of which 0.8% (3, 242) had IBD. Compared to CRC in non‐IBD patients, CRC in IBD patients had longer length of stay (adjusted coefficient (AC) 0.86 days, 95% confidence interval (CI): 0.42, 1.30), more likely developed postoperative complications (adjusted odds ratio (AOR) 1.26, 95% CI: 1.06, 1.50), including postoperative infection (AOR 1.69, 95% CI: 1.20, 2.38) and deep vein thrombosis (AOR 2.42, 95% CI: 1.36, 4.28), and more frequently required blood transfusion (AOR 1.59, 95% CI: 1.30, 1.94). CRC in IBD patients was more likely to be readmitted within 30 days (AOR 1.44, 95% CI: 1.01, 2.04). CONCLUSION: : At a population level, IBD adversely impacts outcomes at the time of CRC surgery.